BIMBINGAN KELOMPOK DENGAN TEKNIK ROLE PLAYING UNTUK MEREDUKSI KEJENUHAN BELAJAR SISWA KELAS VIII H SMP NEGERI 1 PARONGPONG - Aditya Wiguna Sidik; Riesa Rismawati Siddik; Euis Eti Rohaeti (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
Learning burnout as a state of physical, mental, attitudinal and emotional fatigue of individuals or work due to intensive involvement with work over a long period of time which can affect individual performance and achievement and group guidance is basically an activity effort that utilizes group dynamics or a collection of a group of individuals who form a group as a guidance effort carried out and carried out by someone (counselor) with the aim of developing an aspect contained in the individual in the form of attitudes, Then the role playing technique is an effort to help using the role playing method carried out by individuals to play characters or behavior according to the role played by students in obtaining information, knowledge and understanding of self-concept and positive behavior. The purpose of this study was to describe group guidance services with role playing techniques to reduce student learning saturation. This research method is an experimental method with one group pre test - post test. The population in this study were students of class VIII H. the sample used purposive sampling with 7 subjects. The results showed that the level of student learning saturation following group guidance services decreased with role playing techniques, this was indicated by a significance level (2-tailed) of 0.000 <0.05. This shows that there is an effect of the effectiveness of group guidance services with role playing techniques in reducing the boredom of learning class VIII H students at SMP Negeri 1 Parongpong.